Sowjetische Kommandanturen und deutsche Verwaltung in der SBZ und frühen DDR. Dokumente - Foitzik, Jan (Texte und Materialien zur Zeitgeschichte, 2015)
The SBZ and early East German state were subject to a chaotic set of laws derived from the Soviet occupation, Nazi era, German Bundesländer, and new East German government. This source volume helps create order from the chaos. A catalogue of occupational authorities, commanders, and key documents, most of them from Soviet archives, along with introductory texts, examine this history from the Russian as well as German perspectives.